Role of state protectionism in depreciation policy formation - Trachova, Darіa; Трачова, Дар'я Миколаївна; Трачева, Дарья Николаевна (My University, 2017)
The purpose of the paper is generalization of state protectionism measures concerning the depreciation policy formation which have resulted in economic growth in the countries with stable economy and their adaptation to economic conditions of Ukraine.
Keywords: depreciation policy; accelerated depreciation; innovative development; state regulation